L’etica del sopravvissuto nell’estetica di Edith Bruck - Guida, Elisa (Cuadernos de Filología Italiana, 2007)
This work suggests a portrait of Edith Bruck: Hungarian Jewish woman surviving Nazi barbarity, Italian narrator and poet. The analysis, which proceeds in diachronic sense and keeps at a distance the traditional survey methods, aims at characterizing the human and literary course which led the author to the construction of an aesthetics strong of civil commitment. The writing exercise, born as individual means of mourning elaboration, come indeed to the social space of memory and testimony, making of Edith Bruck an Italian writer able to give voice to one of the most dramatic events of 20th century.